Cooperative role of LSD1 and CHD7 in regulating differentiation of mouse embryonic stem cells - Sandhya Malla; Carlos Martinez-Gamero; Kanchan Kumari; Cyrinne Achour; Georgios Mermelekas; David Martinez-Delgado; Alba Coego; Diana Guallar; Angel-Carlos Roman; Francesca Aguilo (Scientific Reports)
Abstract Lysine-specific histone demethylase 1 (LSD1) is a histone demethylase that plays a critical role in epigenetic regulation by removing the methyl group from mono- and di-methylated lysine 4 on histone H3 (H3K4me1/2), acting as a repressor of gene expression. Recently, catalytically independent functions of LSD1, serving as a scaffold for assembling chromatin-regulator and transcription factor complexes, have been identified. Herein, we show for the first time that LSD1 interacts with chromodomain-helicase-DNA-binding protein 7 (CHD7) in mouse embryonic stem cells (ESCs). To further investigate the CHD7–LSD1 crosstalk, we engineered Chd7 and Chd7/Lsd1 knockout (KO) mouse ESCs. We show that CHD7 is dispensable for ESC self-renewal and survival, while Chd7 KO ESCs can differentiate towards embryoid bodies (EBs) with defective expression of ectodermal markers. Intriguingly, Chd7/Lsd1 double KO mouse ESCs exhibit proliferation defects similar to Lsd1 KO ESCs and have lost the capacity to differentiate properly. Furthermore, the increased co-occupancy of H3K4me1 and CHD7 on chromatin following Lsd1 deletion suggests that LSD1 is required for facilitating the proper binding of CHD7 to chromatin and regulating differentiation. Collectively, our results suggest that LSD1 and CHD7 work in concert to modulate gene expression and influence proper cell fate determination.